Pre‐hospital management protocols and perceived difficulty in diagnosing acute heart failure. (8th November 2019) - Harjola, Pia; Miró, Òscar; Martín‐Sánchez, Francisco J.; Escalada, Xavier; Freund, Yonathan; Penaloza, Andrea; Christ, Michael; Cone, David C.; Laribi, Said; Kuisma, Markku; Tarvasmäki, Tuukka; Harjola, Veli‐Pekka; et al.
Abstract: Aim: To illustrate the pre‐hospital management arsenals and protocols in different EMS units, and to estimate the perceived difficulty of diagnosing suspected acute heart failure (AHF) compared with other common pre‐hospital conditions. Methods and results: A multinational survey included 104 emergency medical service (EMS) regions from 18 countries. Diagnostic and therapeutic arsenals related to AHF management were reported for each type of EMS unit. The prevalence and contents of management protocols for common medical conditions treated pre‐hospitally was collected. The perceived difficulty of diagnosing AHF and other medical conditions by emergency medical dispatchers and EMS personnel was interrogated. Ultrasound devices and point‐of‐care testing were available in advanced life support and helicopter EMS units in fewer than 25% of EMS regions. AHF protocols were present in 80.8% of regions. Protocols for ST‐elevation myocardial infarction, chest pain, and dyspnoea were present in 95.2, 80.8, and 76.0% of EMS regions, respectively. Protocolized diagnostic actions for AHF management included 12‐lead electrocardiogram (92.1% of regions), ultrasound examination (16.0%), and point‐of‐care testings for troponin and BNP (6.0 and 3.5%). Therapeutic actions included supplementary oxygen (93.2%), non‐invasive ventilation (80.7%), intravenous furosemide, opiates, nitroglycerine (69.0, 68.6, and 57.0%), and intubation 71.5%. Diagnosing suspected AHF was considered easy to moderate by EMS personnel and moderate to difficult by emergency medical dispatchers (without significant differences between de novo and decompensated heart failure). In both settings, diagnosis of suspected AHF was considered easier than pulmonary embolism and more difficult than ST‐elevation myocardial infarction, asthma, and stroke. Conclusions: The prevalence of AHF protocols is rather high but the contents seem to vary. Difficulty of diagnosing suspected AHF seems to be moderate compared with other pre‐hospital conditions.